PENINGKATAN PRODUKSI BENIH G0 KENTANG MELALUI MODIFIKASI TEKNOLOGI BUDIDAYA - Kiki Kusyaeri Hamdani; Meksy Dianawati (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2021)
Efforts to procure quality potato seeds are continuously being made, including using plantlet cuttings to produce G0 seeds. Several cultivation technologies can be used to increase the quality and quantity of G0 potato seeds. This study aims to increase the production of G0 potato seeds through modification of cultivation technology, namely planting media, number of cuttings, planting, and hood. The research was conducted from November 2017 to March 2018 in a plastic house in Lembang, West Bandung, West Java with an altitude of 1.200 m above sea level. The experiment used a completely randomized block design (RCBD) with eight treatments and ten replications. The variety used was Granola L. The results showed that the best modification of cultivation technology to increase the production of the number of tubers per G0 potato plant was a mixture of soil, manure, roasted husk (1: 1: 1) + heaping + 2 seeds + without hoods.